PERTUNJUKAN MUSIK GRANDE OUVERTURE, ASTURIAS, DAN KARAK LILISAN DALAM SOLO GITAR - Supriando Supriando (Puitika, 2016)
Musical performances Grande Ouverture, Asturias, and Karak Lilisan in a guitar solo is instrumental performances by classical guitar performer who puts as the sole major player in a musical performance. A performances that shows the maturity of the skill of a player on the composition of the music being played. Mechanical performances that have a distinctive character of a soloist who gives a new feel without forgetting the values desired musical composers to a composition played. Keywords: Grande Ouverture, Asturias, Karak Lilisan, guitar